Radiation-Induced Cardiotoxicity in Hypertensive Salt-Sensitive Rats: A Feasibility Study - Dayeong An; Alison Kriegel; Suresh Kumar; Heather Himburg; Brian Fish; Slade Klawikowski; Daniel Rowe; Marek Lenarczyk; John Baker; El-Sayed Ibrahim (Life)
Radiation therapy (RT) plays a vital role in managing thoracic cancers, though it can lead to adverse effects, including significant cardiotoxicity. Understanding the risk factors like hypertension in RT is important for patient prognosis and management. A Dahl salt-sensitive (SS) female rat model was used to study hypertension effect on RT-induced cardiotoxicity. Rats were fed a high-salt diet to induce hypertension and then divided into RT and sham groups. The RT group received 24 Gy of whole-heart irradiation. Cardiac function was evaluated using MRI and blood pressure measurements at baseline, 8 weeks and 12 weeks post-RT. Histological examination was performed after the last timepoint or animal death. The hypertensive RT rats demonstrated significant decreases in left-ventricular ejection fraction (EF) (45 ± 7.2%) compared to sham (68 ± 7.3%). Furthermore, circumferential (Ecc) and radial (Err) myocardial strains were significantly reduced (Ecc: −7.4 ± 2.0% RT rats vs. −11 ± 2.4% sham; Err: 15 ± 6.5% RT rats vs. 23 ± 8.9% sham). Histological analysis revealed significant pathophysiological remodeling post-RT, including nuclear size, interstitial fibrosis, necrosis, and the presence of inflammatory cells. This study provides valuable insights into the cardiotoxic effects of RT in the context of hypertension, highlighting the potential of using MRI for improved risk assessment with potential for future clinical translation.